Anterior third ventricular height and infundibulochiasmatic angle: two novel measurements to predict clinical success of endoscopic third ventriculostomy in the early postoperative period - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2020)
OBJECTIVE The authors sought to develop a set of parameters that reliably predict the clinical success of endoscopic third ventriculostomy (ETV) when assessed before and after the operation, and to establish a plan for MRI follow-up after this procedure. METHODS This retrospective study involved 77 patients who had undergone 78 ETV procedures for obstructive hydrocephalus between 2010 and 2015. Constructive interference in steady-state (CISS) MRI evaluations before and after ETV were reviewed, and 4 parameters were measured. Two well-known standard parameters, fronto-occipital horn ratio (FOHR) and third ventricular index (TVI), and 2 newly defined parameters, infundibulochiasmatic (IC) angle and anterior third ventricular height (TVH), were measured in this study. Associations between preoperative measurements of and postoperative changes in the 4 variables and the clinical success of ETV were analyzed. RESULTS Of the 78 ETV procedures, 70 (89.7%) were successful and 8 (10.3%) failed. On the preoperative MR images, the mean IC angle and anterior TVH were significantly larger in the successful procedures. On the 24-hour postoperative MR images of the successful procedures, the mean IC angle declined significantly from 114.2 degrees to 94.6 degrees (p < 0.05) and the mean anterior TVH declined significantly from 15 to 11.2 mm (p < 0.05). The mean percentage reduction of the IC angle was 17.1%, and that of the anterior TVH was 25.5% (both p < 0.05). On the 1-month MR images of the successful procedures, the mean IC angle declined significantly from 94.6 degrees to 84.2 degrees (p < 0.05) and the mean anterior TVH declined significantly from 11.2 to 9.3 mm (p < 0.05). The mean percentage reductions in IC angle (11%) and anterior TVH (16.9%) remained significant at this time point but were smaller than those observed at 24 hours. The 6-month and 1-year postoperative MR images of the successful group showed no significant changes in mean IC angle or mean anterior TVH. Regarding the unsuccessful procedures, there were no significant changes observed in IC angle or anterior TVH at any of the time points studied. Reduction of IC angle and reduction of anterior TVH on 24-hour postoperative MR images were significantly associated with successful ETV. However, no clinically significant association was found between FOHR, TVI, and ETV success. CONCLUSIONS Assessing the IC angle and anterior TVH on preoperative and 24-hour postoperative MR images is useful for predicting the clinical success of ETV. These 2 measurements could also be valuable as radiological follow-up parameters.
Keywords: endoscopic third ventriculostomy; hydrocephalus; optic chiasm; infundibulum; third ventricle; success; OCCIPITAL HORN RATIO; SIZE; HYDROCEPHALUS; 3RD-VENTRICULOSTOMY; FAILURE; VOLUME; OUTCOMES; SHAPE